Influence of livelihood functional diversity on agro-food systems in rural communities from different macro regions of Brazil - Rodrigo Jesus Silva; Gabriela Bielefeld Nardoto; Luiz Antônio Martinelli (Environmental and Sustainability Indicators)
Urbanization has changed the livelihood diversity of rural communities worldwide. This study aimed to fit an indicator of the functional diversity of livelihood activities to assess the heterogeneity of socioeconomic conditions and their influence on agro-food changes in rural communities in Brazil. This study was conducted in three macro regions of Brazil, through semi-structured questionnaire interviews conducted in 1012 households to verify details about food patterns, self-consumption farms, and socioeconomic conditions. Data from questionnaires were analyzed using multivariate statistical models to appraise similarities among communities and determine the relative influence of socioeconomic factors on agro-food patterns. Specific socioeconomic status and use of natural resource data were analyzed while adjusting for Petchey and Gaston's indicator of functional diversity to evaluate the heterogeneity of local livelihood activities and socioeconomic conditions. This indicator summarizes the proportional livelihood richness in all sampled places, as better conditions for survival were found in specific localities of the central-west and eastern Amazon regions of Brazil. We also verified that the remote areas of the Goiás and Pará states were regions with the most significant maintenance of traditional food habits and use of natural resources. Although these results do not allow us to establish that all of these areas are undergoing an agro-food transition process, some localities are more likely than others to adjust their livelihood strategies to face global food changes. This interdisciplinary approach facilitated the identification of the most similar groups regarding their livelihoods and socioeconomic conditions that influenced the agro-food transition process in rural regions.